A study of operational decisions of city gas operators under the energy metering and pricing model - Wan, Qin; Sun, Yang; Wen, Li; Qi, Can; Yu, Cuiting (Frontiers in Energy Research, 2024)
This paper establishes a mathematical model based on optimization theory to explore the operational decisions of city gas suppliers in the volumetric and energy metering and pricing modes, respectively, under the condition of relatively stable natural gas sales price. Compared with the volumetric pricing model, the quantitative condition that the energy metering pricing model can simultaneously increase the profit of gas merchants and the consumer surplus of gas users is proposed. It is found that the quantitative condition is related to the standard unit calorific value of natural gas stipulated by the National Development and Reform Commission (NDRC) and other relevant governmental departments in the energy metering pricing model, among other factors. Under the energy metering pricing model, the NDRC and other authorities can theoretically influence the incentives of gas producers and guide the preference of gas users for natural gas energy metering pricing by regulating the standard unit calorific value of natural gas. Further derived equations for the derivation of a reasonable range of standard unit calorific values for natural gas. The findings of this paper provide theoretical support for advancing natural gas energy measurement and pricing reform.